Tubal ligation and endometrial Cancer risk: a global systematic review and meta-analysis - Loghmani, Laleh (BMC Cancer, 2019)
BACKGROUND: Studies on relationship between tubal ligation and endometrial cancer have led to contradictory findings. In several studies, however, a reduced endometrial cancer risk was suggested following tubal ligation. Therefore, a systematic review and meta-analysis was conducted to examine the relationship between tubal ligation and endometrial cancer risk. METHODS: In this systematic review and meta-analysis, PubMed/Medline, Web of Science, Scopus, Embase, and Google Scholar were searched for relevant studies published up to May 30th, 2018. We compared endometrial cancer risk in women with and without tubal ligation in retrieved studies. RESULTS: Two hundred nine studies were initially retrieved from the data bases. After exclusion of duplicates and studies which did not meet inclusion criteria, ten cohort and case-control studies, including 6,773,066 cases, were entered into the quantitative meta-analysis. There was 0.90% agreement between two researchers who searched and retrieved the studies. The summary OR (SOR) was reported using a random effect model. Begg’s test suggested that there was no publication bias, but a considerable heterogeneity was observed (I(2) = 95.4%, P = 0.001). We pooled the raw number of tables cells (i.e. a, b, c, and d) of eight studies. The SOR suggested that tubal ligation was significantly associated with a lower risk of endometrial cancer (SOR = 0.577, 95% CI = 0.420–0.792). Also, given the rare nature of endometrial cancer (< 5%), different effect sizes were considered as comparable measures of risk. Therefore we pooled ten studies and SOR of these studies revealed that tubal ligation was significantly associated with a lower risk of endometrial cancer (SOR = 0.696, 95% CI = 0.425–0.966). Besides that, we pooled eight studies in which adjusted effect sizes were reported and a subsequent analysis revealed that the summary estimate of adjusted odds ratio (SAOR) was significant (SAOR = 0.862, 95% CI = 0.698–1.026). CONCLUSIONS: This study revealed a protective effect of tubal ligation on endometrial cancer risk (approximately 42% lower risk of cancer). It is recommended that studies should be designed to reveal mechanisms of this relationship.